تصحيح المفاهيم الخاصة بالجهاد ودوافعه: دراسة تحليلية معاصرة من خلال سورة الأنفال - Nabilah binti Mohd Ali (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
The research aims at correcting the concepts of Jihad and its justifications through a contemporary analytical study of Surah al-Anfal. A number of misconceptions about Jihad and the reasons that led to it were identified, addressed and further corrected in the thesis. In addition to disclosing the justifications for Jihad in its variety, this research also highlights the Qura'nic approach on the motives of Jihad that is present in Surah al-Anfal. Two scientific methods were adopted throughout this research, which are; firstly, the extrapolation method wherein Jihad related verses which were extrapolated from the Holy Quran, in particular, the verses of Surah al-Anfal, and references from traditional and contemporary exegesis of the Qur'an (Kutub al-TafÉsir) pertaining to the various motives of Jihad were put into study. The second method is the analytical method that involves utilizing and analysing the said verses and comparing between different opinions of scholars. These methods enable the most important opinions regarding the motives of Jihad to be educed. Additionally, the researcher also addresses the extremists' point of view on the subject and addressed them by correcting their concepts on the motives of Jihad. Among the results deduced from this study is an emphasis on the wider concept and scope of Jihad, which is more than armed struggle per se. In fact, this research has managed to identify various valid motives for Jihad as mentioned in Surah al-Anfal such as the motives of Jihad for the sake of Allah rather than the mundane interests that drives a person to fight. However, not all justifications are acceptable by Shari'ah. It is also important to note the misinterpretation of the Quranic verses and the prophetic Hadiths is among the major factors that lead to misunderstanding of Jihad. Therefore, a Muslim must have a profound understanding of this rule before putting it into application.